Measuring poverty within the household - Caitlin Brown; Jacob Penglase; Rossella Calvi; Denni Tommasi (IZA World of Labor, 2022)
A key element of anti-poverty policy is the accurate identification of poor individuals. However, measuring poverty at the individual level is difficult since consumption data are typically collected at the household level. Per capita measures based on household-level data ignore both inequality within the household and economies of scale in consumption. The collective household model offers an alternative and promising framework to estimate poverty at the individual level while accounting for both inequality within the household and economies of scale in consumption.
Keywords: I3; I32; 330; poverty; equivalence scales; intra-household inequality; collective model; resource shares; scale economies